2022
DOI: 10.3390/molecules27165174
|View full text |Cite
|
Sign up to set email alerts
|

In Silico and In Vitro Studies of Alchemilla viridiflora Rothm—Polyphenols’ Potential for Inhibition of SARS-CoV-2 Internalization

Abstract: Since the outbreak of the COVID-19 pandemic, it has been obvious that virus infection poses a serious threat to human health on a global scale. Certain plants, particularly those rich in polyphenols, have been found to be effective antiviral agents. The effectiveness of Alchemilla viridiflora Rothm. (Rosaceae) methanol extract to prevent contact between virus spike (S)-glycoprotein and angiotensin-converting enzyme 2 (ACE2) and neuropilin-1 (NRP1) receptors was investigated. In vitro results revealed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Broadly speaking, flavonoids such as myricetin are some of the most promising natural drug candidates for antiviral development. Multiple studies have demonstrated the S-ACE2 inhibitory activity of compounds such as epicatechin, luteolin, curcumin, and quercetin using a variety of in vitro and in silico methodologies ( Goc et al., 2021b ; Zhan et al., 2021 ; Al-Shuhaib et al., 2022 ; Chen C. et al., 2022 ; Nag et al., 2022 ; Ohishi et al., 2022 ; Suručić et al., 2022 ; Gao et al., 2023 ; Zhu et al., 2023 ). Other polyphenolic compounds display similar potential, including ellagitannins and carboxylic acids which have some of the most potent S-ACE2 IC 50 values in recent literature, often in the nanomolar range ( Table 3 ) ( Mei et al., 2021 ; Invernizzi et al., 2022 ).…”
Section: Drug Discovery From Natural Productsmentioning
confidence: 99%
“…Broadly speaking, flavonoids such as myricetin are some of the most promising natural drug candidates for antiviral development. Multiple studies have demonstrated the S-ACE2 inhibitory activity of compounds such as epicatechin, luteolin, curcumin, and quercetin using a variety of in vitro and in silico methodologies ( Goc et al., 2021b ; Zhan et al., 2021 ; Al-Shuhaib et al., 2022 ; Chen C. et al., 2022 ; Nag et al., 2022 ; Ohishi et al., 2022 ; Suručić et al., 2022 ; Gao et al., 2023 ; Zhu et al., 2023 ). Other polyphenolic compounds display similar potential, including ellagitannins and carboxylic acids which have some of the most potent S-ACE2 IC 50 values in recent literature, often in the nanomolar range ( Table 3 ) ( Mei et al., 2021 ; Invernizzi et al., 2022 ).…”
Section: Drug Discovery From Natural Productsmentioning
confidence: 99%